Problem of terminology in conservation and restauration - Benkouider, Samia (International Journal of Psychosocial Rehabilitation, 2022)
This research tackles the problem of determining and translating technical terms, in particular the terms of conservation and restauration. This is due in one hand to the difficulty of limiting their meanings in a defined frame, and on the other hand finding an appropriate translation to them, in addition to the divergence between the different schools in this domain which is based on a classy thought that aims to protect the human heritage, by relying on the technical and philosophical aspects at the same time. Accordingly, we have opted to tackle this domain as an attempt to determine the notions and bases in order to restrict the terminology used in the language of this specialization, so that we can find appropriate solutions to them and highlight the necessity to reach agreement on them to get rid of any ambiguity in future.